Diagnóstico socioeconómico de los propietarios de los microemprendimientos ubicados en la calle Olmedo sector centro de la ciudad de Esmeraldas - García Rojas, Luis Enrique (2023)
In recent years, entrepreneurship in Ecuador and other Latin American countries for different reasons is suffering a great decline, additionally the city of Esmeraldas is plunged into a wave of violence that directly affects business, important reasons that have motivated the lifting of this Socioeconomic diagnosis for micro-entrepreneurs on Olmedo Avenue, one of the most important and commercial arteries in the city center. This work was prepared using a mixed approach methodology and based on a descriptive investigation. The research techniques applied were an observation sheet, survey and interview. As a consequence, it was shown that: